Implementation of Cryptographic Algorithm on IoT Device’s ID - Aditya Kurniawan; Ratna Mayasari; Muhammad Ary Murti (APIC, 2018)
Data security is one of many problems that we face in IoT implementation. One of the problems with data security is we cannot assure that the data we received in the server-side is truly our data that we send from client-side or sensor-side. With that problems, comes some solutions like encryption and decryption method or some basic authentication planted on the server-side. In this research, we propose some encryption and decryption method that can be easily implemented on both server and sensor-side and then we analyze the complexity of its algorithm. This research aims to create some authentication process for the data that server-side receive from the sensor-side by creating encrypted ID consisting of 6 digits of alphanumeric and useful for identification process in system, so the server can recognize the data and validate it.